2021
DOI: 10.1002/jlb.1mia0321-164r
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cell-derived extracellular vesicles inhibit neuroblastoma growth by regulating GABBR1 activity through LINC00622-mediated transcription factor AR

Abstract: Neuroblastoma (NB) is a huge threat to children's health. Adipose-derived stem cellsderived extracellular vesicles (ADSC-Evs) can regulate tumor progression. This study aimed to identify the role of ADSC-Evs in NB. Following ADSC-Ev isolation and identification, PKH26-labeled ADSC-Evs were cocultured with NB cells to observe the internalization of ADSC-Evs. ADSC-Ev effects on NB cell proliferation, invasion, and migration were assessed. The regulatory molecules related to NB development were predicted. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recent research showed that ADAMTS9-AS2 could restrict the deterioration of esophageal cancer and it also has the ability to function as a prognostic lncRNA in LUAD [ 39 ]. As to LINC00622, it is tightly associated with transcriptional factor androgen receptor and essential neuroblastoma progression [ 40 ]. Notably, MIR99AHG not only can influence the epithelial-mesenchymal transition in LUAD but also encourage the differentiation of bone marrow mesenchymal stem cells [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that ADAMTS9-AS2 could restrict the deterioration of esophageal cancer and it also has the ability to function as a prognostic lncRNA in LUAD [ 39 ]. As to LINC00622, it is tightly associated with transcriptional factor androgen receptor and essential neuroblastoma progression [ 40 ]. Notably, MIR99AHG not only can influence the epithelial-mesenchymal transition in LUAD but also encourage the differentiation of bone marrow mesenchymal stem cells [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research showed that ADAMTS9-AS2 could restrict the deterioration of esophageal cancer and it also has the ability to function as a prognostic lncRNA in LUAD [39]. As to LINC00622, it is tightly associated with transcriptional factor androgen receptor and essential neuroblastoma progression [40]. Notably, MIR99AHG not only can in uence the epithelial-mesenchymal transition in LUAD but also encourage the differentiation of bone marrow mesenchymal stem cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-431-5p carried by umbilical cord MSC-derived sEVs demonstrated inhibitory effects on PRDX1 , including restricted CRC cell line growth [ 67 ]. LINC00622 included in adipose-derived stem cell-derived sEVs promoted gamma-aminobutyric acid B-type receptor 1 and inhibited neuroblastoma cell growth [ 68 ]. Plant-derived sEVs also demonstrated anti-tumor effects.…”
Section: Sevs As An Active Pharmaceutical Ingredient For Cancer Therapymentioning
confidence: 99%